2005
DOI: 10.1002/rcm.2285
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of 1‐propanol and 2‐propanol in humid air samples using selected ion flow tube mass spectrometry

Abstract: Following the observation that propanol is present in the breath samples of cystic fibrosis (CF) patients infected by Pseudomonas aeruginosa (PA), a study of the reactions of H(3)O(+), NO(+) and O(2) (+.) with 1-propanol and 2-propanol has been conducted using selected ion flow tube mass spectrometry (SIFT-MS). In this study the number and the distribution of the product ions from NO(+) reactions with the two propanol isomers under humid air conditions were able to differentiate between the two isomers. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 48 publications
(69 reference statements)
0
20
1
1
Order By: Relevance
“…Previous reports have linked dimethyl sulfide and isoprene to cystic fibrosis and respiratory exacerbation (Barker et al, 2006;Kamboures et al 2005;McGrath et al, 2000). However, the present results indicate no significant difference between dimethyl sulfide and isoprene in the cystic fibrosis ( (Wang et al, 2006;Enderby et al, 2009). Throughout this trial the signals in the corresponding mass channels never exceeded ambient levels in line with no identified P. aeruginosa infection.…”
Section: Direct Ptr-tof-ms Applied To Fingerprinting Breathcontrasting
confidence: 46%
“…Previous reports have linked dimethyl sulfide and isoprene to cystic fibrosis and respiratory exacerbation (Barker et al, 2006;Kamboures et al 2005;McGrath et al, 2000). However, the present results indicate no significant difference between dimethyl sulfide and isoprene in the cystic fibrosis ( (Wang et al, 2006;Enderby et al, 2009). Throughout this trial the signals in the corresponding mass channels never exceeded ambient levels in line with no identified P. aeruginosa infection.…”
Section: Direct Ptr-tof-ms Applied To Fingerprinting Breathcontrasting
confidence: 46%
“…2-Propanol, an enzyme-mediated product of reduction of acetone, was demonstrated in a breath sample from one patient with CF infected with Pseudomonas aeruginosa 31. We speculate that the elevated EBC ethanol concentrations in patients with CF may be related to the reduced capacity of Pseudomonas aeruginosa to oxidise ethanol to acetate,32 whereas the elevated EBC 2-propanol concentration might be due to bacterial metabolism and/or increased lipolysis and lipid peroxidation 31. Elevated EBC acetate concentrations in healthy subjects could reflect metabolism of oral resident bacteria such as Streptococcus mutans , which degrades pyruvate into end products of metabolism including acetate and lactate 33…”
Section: Discussionmentioning
confidence: 98%
“…Using 1 H-NMR, acetone was detected in the bronchoalveolar lavage fluid of children with CF with varying levels of inflammation 13. 2-Propanol, an enzyme-mediated product of reduction of acetone, was demonstrated in a breath sample from one patient with CF infected with Pseudomonas aeruginosa 31. We speculate that the elevated EBC ethanol concentrations in patients with CF may be related to the reduced capacity of Pseudomonas aeruginosa to oxidise ethanol to acetate,32 whereas the elevated EBC 2-propanol concentration might be due to bacterial metabolism and/or increased lipolysis and lipid peroxidation 31.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate this, a study has been made ) of the ion chemistry of H 3 O þ and NO þ with the propanol isomers, acetic acid and methyl formate under varying conditions of sample humidity up to that of exhaled breath (6% by volume). The problems involved in the separate analysis of propanol had been met and solved by previous SIFT-MS studies (Š paněl & Smith, 1997;Wang et al, 2006) and now the study by Pysanenko, Š paněl, and Smith (2009) revealed how acetic acid and methyl formate can be separately identified in a humid mixture using NO þ precursor ions. Following this work, the kinetics library for the SIFT-MS analyses of these compounds in breath was constructed and the analysis of the exhaled breath of five healthy volunteers showed that acetic acid was present at levels typically within the range from 30 to 50 ppb and that methyl formate was not present above the detection limit.…”
Section: Recent Extensions To Sift-msmentioning
confidence: 98%